2010
DOI: 10.1007/978-3-642-04231-7_14
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Pediatric Cancer Survivorship

Abstract: Owing to improved treatment pro-tocols in the last 25 years there have been dramatic improvements in the 5-year relative survival rate of the most prevalent childhood cancers. For instance, the 5-year relative survival rate among children for all cancer sites combined, improved from 58% to 80% in patients diagnosed in 1975-1977 and in 1996-2004 respectively. However, as survival rates have improved, there has been an increasing recognition of adverse short and longer term effects associated with treatment and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
65
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 89 publications
0
65
0
6
Order By: Relevance
“…In addition, relevant child-specific outcomes and appropriate assessments must be determined to evaluate the holistic effects of therapeutic exercise specifically on childhood cancer patients. Consequently, as presented in other reviews, the current literature not only provides promising results but also reveals challenges to be faced in the future (3,12,13,15,16).…”
Section: Review Baumann Et Almentioning
confidence: 86%
See 2 more Smart Citations
“…In addition, relevant child-specific outcomes and appropriate assessments must be determined to evaluate the holistic effects of therapeutic exercise specifically on childhood cancer patients. Consequently, as presented in other reviews, the current literature not only provides promising results but also reveals challenges to be faced in the future (3,12,13,15,16).…”
Section: Review Baumann Et Almentioning
confidence: 86%
“…A s a result of improved treatment regimes in pediatric oncology, the survival rates of children with cancer have risen to ~80% for 5-y survival (1)(2)(3)(4). Therefore, the population of childhood cancer survivors is constantly growing.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing evidence for the positive effects of aerobic exercise training on physical fitness, fatigue and physical well-being of children during and after treatment for cancer [19,26,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…A study done by Wolin et al [21] found significant improvements in muscle strength, functional mobility, aerobic fitness and QoL after implementation of an 8-week intervention combining aerobic and resistance exercises. To gauge similar benefits in the current study, we targeted these areas in weeks 3, 4, 5, and 7.…”
Section: Video Set-upmentioning
confidence: 99%